2010
DOI: 10.1016/j.physbeh.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Interparental aggression and parent–adolescent salivary alpha amylase symmetry

Abstract: The present study examined salivary alpha-amylase (sAA), a putative marker of adrenergic activity, in family members engaging in family conflict discussions. We examined symmetry among family members' sAA levels at baseline and in response to a conflict discussion. The relation between a history of interparental aggression on parent-adolescent sAA symmetry also was examined. Participants were 62 families with a mother, father, and biological child age 13-18 (n = 29 girls). After engaging in a relaxation proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 46 publications
6
39
1
Order By: Relevance
“…In addition, measuring cortisol over several days would provide an assessment of intra-individual differences in situations of high versus low interpersonal stress. Other clinically relevant future research suggested here includes whether interventions would lead to increased HPA reactivity in adolescents after internalizing symptoms lessen [37], and whether, by incorporating observational measures, we would find concordance between behavioral measures of stress, self-reported stress, and systems of physiological stress [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, measuring cortisol over several days would provide an assessment of intra-individual differences in situations of high versus low interpersonal stress. Other clinically relevant future research suggested here includes whether interventions would lead to increased HPA reactivity in adolescents after internalizing symptoms lessen [37], and whether, by incorporating observational measures, we would find concordance between behavioral measures of stress, self-reported stress, and systems of physiological stress [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…These topics were presented to the family to guide the 15‐minute family discussion. Families were instructed to do the following: discuss the highest conflict topic first, ensure that each individual expressed his/her point of view, and discuss the problem as they normally would (See Gordis, Margolin, Spies, Susman, & Granger, , for further details). To directly assess the similarity of the conflict discussions to families' discussions outside the laboratory, we administered a questionnaire immediately after the discussion on which participants rated the following question: “How similar was this discussion to other family discussions you have had?” Based on a 0 (not at all similar) to 4 (very similar) response scale, husbands' mean rating was 2.7 and wives' was 2.9, indicating laboratory discussions moderately similar to at‐home conflicts.…”
Section: Methodsmentioning
confidence: 99%
“…Gordis et al (2010) studied family members’ biological stress responses to a family conflict discussion task. Adolescents from families with a history of interparental aggression showed a reactive response to the task, indicated by elevations in sAA, compared with adolescents from families with no family history of interparental aggression.…”
Section: Introductionmentioning
confidence: 99%